Efektivitas Penerapan Sistem Informasi Desa di Desa Delima Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat Jambi (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze the effectiveness of the Village Information System in Delima Village as one of the village government's efforts to improve the quality of public services. The study used qualitative methods with descriptive research and data collection techniques such as observation, interviews, and documentation. The results of the study indicate that the implementation of the Village Information System in Delima Village has not been running effectively. Although this system has been used for administrative activities such as issuing certificates, managing population data, and disseminating village information, its implementation still faces various obstacles. Some of these inhibiting factors include limited human resources who have not fully mastered technology, lack of training for village officials, and unstable internet connections throughout the village. As a result, services through the Village Information System are not optimal and have not yet fully benefited the community. Therefore, it is necessary to increase the capacity of village officials and provide infrastructure support so that the implementation of the Village Information System in Delima Village can run more effectively in the future.